Metabolic syndrome among a Ghanaian cohort living with HIV initiated on dolutegravir in a real-world setting: a prospective study - Kofi Agyabeng; Ernest Kenu; Kwasi Torpey; Stephen Ayisi Addo; Vincent Ganu; Magdalene Akos Odikro; Raphael Adu-Gyamfi; Abdul Gafaru Mohammed; Margaret Lartey (BMJ Open)
Objectives The use of antiretroviral therapy has been linked to the development of some components of metabolic syndrome (MetS), specifically glucose intolerance, weight gain and defective lipid metabolism. This study determined the relationship between dolutegravir (DTG) and MetS in a cohort of persons living with HIV (PWH) initiating DTG-based regimen in Ghana.Design A 2-year observational prospective study was conducted from September 2020 to August 2022.Setting Five HIV high-burden facilities providing antiretroviral therapy services at the district and tertiary levels of care in Ghana.Participants Persons with HIV who were newly enrolled onto DTG.Primary and secondary outcome measures Waist circumference, body mass index, blood pressure, fasting blood glucose and lipids were the primary outcomes measured at baseline, 3, 6, 12 and at 18 months follow-up to determine the incidence of MetS. MetS was defined using the Joint Consensus definition that combines the International Diabetes Federation and the National Cholesterol Education Programme Adult Treatment Panel III (ATP III) definitions. The Kaplan-Meier estimator was used to estimate the risk of developing MetS. The Cox proportional hazard model was used in estimating HRs.Results Of 3664 PWH screened at baseline, 31.4% (1152/3664) had MetS. Of the remaining 2512 with no MetS at baseline, there were 960 incident cases of MetS over the 1.5 years follow-up. The estimated MetS incident rate is 384.2 (95% CI: 360.6 to 409.2) per 1000 person-years with a median time to development of MetS at 6 months (IQR; 3–12 months). Being female (adjsuted HR, aHR: 1.42, 95% CI: 1.19 to 1.70), age ≥50 years (aHR: 1.30, 95% CI: 1.12 to 1.51), having a comorbidity at baseline (aHR: 1.39, 95% CI: 1.12 to 1.51) and being overweight (aHR: 1.46, 95% CI: 1.25 to 1.71) and obese (aHR: 1.62, 95% CI: 1.36 to 1.93) were associated with higher risk of MetS development.Conclusions The incidence of MetS was high among our patients, with elevated fasting blood sugar and elevated blood pressure being the most common developed MetS defining components. HIV programmes should institute targeted interventions at addressing central obesity to reduce the risk of MetS.